Analisis Kadar Siklamat Pada Selai Tidak Bermerek Yang Dijual Di Pasar Tradisional Kota Makassar - Muawanah, Muawanah; Nurhidayat, Nurhidayat; Rasyid, Nur Qadri; Susanti, Susi (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2020)
The jam is a semi-solid food made from fruit or other processed product. The manufacturing process can add food additives (BTP), one of which is artificial sweeteners such as cyclamate. Cyclamate can be harmful to health if consumed in levels that exceed the maximum limit.The purpose of this research was to identificate and determine the cyclamate content of unbranded jam in the traditional market town of makassar. The type of research used is laboratory observation with simple random sampling technique. This research was conducted qualitatively (depositional method) and quantitatively (gravimetric method). Based on the results of the research from 7 (seven) samples of unmerck jam there were 2 (two) positive samples containing cyclamate with cyclamate levels obtained, namely the K sample 0f 42.273,78 mg/kg and sample T3 of 49, 822. 67 mg/kg. In this study it can be concluded that 2 (two) samples of unbranded jam contained cyclamate levels that exceed the maximum limit set by BPOM No. 4 of 2014, namely 1000 mg/kg and so it is not safe for consumption.